Transcriptional regulation as a dose-dependent process: insights from transcription factor tuning - Gemma Noviello (Open Biology)
Several biological processes, including transcriptional regulation by transcription factors (TFs), are dose-dependent. At the mathematical level, dose-dependent processes can be modelled by fitting dose–response curves, for istance, employing Hill-type equations. At the experimental level, however, quantitatively regulating, or tuning, endogenous gene expression to characterize dose-dependent processes is challenging. Here, existing methods to fine-tune endogenous gene expression are compared and contrasted. Relatively small TF dosage variations have been shown to underpin cell fate decisions. Nonetheless, the current understanding of the molecular mechanisms by which TFs quantitatively regulate gene expression is limited, due to the paucity of genome-wide studies in endogenous and physiological conditions. Recent works combining quantitative perturbations of TFs and genome-wide response analyses are untangling an underexplored layer of transcriptional control. At the same time, new questions are emerging in the field, which will require further technological advancements in order to be addressed.